Towards a Renewed University History: UGentMemorie and the Merits of Public History, Academic Heritage and Digital History in Commemorating the University - Danniau, Fien; Mantels, Ruben; Verbruggen, Christophe (Studium, 2013)
In this article we consider alternative ways to remember the university in the twenty-first century. Drawing from insights in (1) public history, (2) academic heritage and (3) digital history, we explore ways to fill in the gap between historians and communicators, the demands of science and the expectations of the public. The insights and many of the examples given are derived from our experiences with UGentMemorie, the virtual memory of Ghent University (www.UGentMemorie.be), which functions as a preparation platform for its bicentennial in 2017. We argue that public and digital history are interesting ways to communicate research on university history and heritage on different levels on the one hand and to integrate in a sensible way the academic culture of remembrance in a historical project on the other. In terms of output, this means that the classic publication of the complete history of the university at least has to be accompanied by other initiatives, such as smaller occasional publications, exhibitions or heritage walks, digital output and social media strategies.